The Effects of using a Stationary Program, Local Entertainment Program, and a Mix of Stationary and Local Entertainment Program on the Physical Fitness of Prathomsuksa 1 Students - อุตมังค์ กิตติพร; ทวีสุข ดวงไกร; ปินะกาลัง สังเวียน (Journal of Roi Et Rajabhat University, 2016)
This research was designed to (1) compare physical fitness within a group at pre– training, after 4th and 8th weeks of training for stationary (ST), local entertainment (LET), and mixed of stationary and local entertainment (MSLET) program group. And, (2) compare physical fitness between groups of ST, LET, and MSLET program at pre–training, after 4th and 8th weeks of training. The study sample consisted of 48 Prathomsuksa 1 students, aged 6–7 years. The participants were divided into three experimental groups, 16 students for each group by using 1 class room randomly assigned to each group. Research instruments included ST, LET and MSLET programs. Also, five items of physical fitness testing were selected. Statistics in data analysis composed of mean and standard deviation, Friedman test, and Nonparametric Kruskal–Wallis one–way ANOVA with repeated measure. This research found that the physical fitness within and between 3 groups were significantly different at .05. The ST program improved abdominal muscle strength. The LET program improved speed ability. The MSLET program can improve agility and flexibility. Moreover, the MSLET program was influenced the different the abdominal muscle strength and speed between after 4th and 8th weeks of training that better than the only ST and LET program. In conclusion, the MSLET program was better improved leg muscle power, agility, flexibility, abdominal muscle strength and speed than ST and LET program.